Molecular and quantitative analysis of beef cattle breeds in Malaysia - Majidi, Alireza (2014)
The Malaysian beef industry is an important component of the livestock sector, producing animal food protein for the population. Growth and carcass traits are economically important traits of beef cattle and are under the control of multiple genes. The estimation of genetic parameters is an integral part of livestock breeding to predict possible outcomes based on selection objectives, but this requires proper record keeping. Genetic markers in candidate genes for traits of interest in beef animals may be useful in marker-assisted selection. The objective of the present project was to evaluate some beef cattle breeds in Malaysia using molecular markers and to evaluate the Brakmas breed using quantitative genetics method. In the first study, 20 single nucleotide polymorphism loci (SNP) DNA markers at candidate genes for growth and meat quality traits were investigated for seven cattle breeds, namely the Kedah Kelantan (KK), Brakmas, Brangus, Cheroke, Nellore, and two KK non descript crosses (KKC1 and KKC2). The candidate genes assessed were leptin (1,2,3), Diglyceride aciltransfrase (DGAT1), Calpastatin, Calpastatin promoter, Myostatin, Growth hormone (GH), Growth hormone receptor (GHR), Insulin-like growth factor binding protein (IGFBP1, IGFBP2), Growth hormone releasing hormone (GHRH), Beta-Lactoglobulin (LGB), Tyroglobulin (TG), Lipoprotein lipase (LPL), Heat shock protein70 (HSP70), Calpain (1,2), Growth hormone three (GH3) and Neurotensin. DNA extracted from blood samples of 50 animals of each breed (except for Brangus n=17) were analysed for the targeted loci using PCRRFLP. Of the total of 20 loci, 15 were polymorphic and five monomorphic in all breeds. Significant differences were found between the KK, KK crosses and exotic breeds at CAST, with the KK and KK crosses showing a higher frequency of the favorable A allele, which has been reported to be positively correlated with meat tenderness. High polymorphism was observed in Brangus (75%), KK and Charoke (70%), Brakmas and KKC1 (60%), and Nellore (55%); the lowest was in KKC2 (45%). High number of fixed alleles were obtained for KKC2 (11 alleles), KKC1, Brakmas and Nellore (8 alleles), and KK and Charoke (6 alleles); Brangus has fixation of five alleles. The highest total heterozygosity is exhibited by Brakmas (0.39±0.42) and lowest heterozygosity by KKC1 (0.20±0.28). The highest heterozygosity was observed for CAST in Brakmas and KK (0.88 and 0.86, respectively), CALP1 in Brakmas (0.60), GHR in Nellore (0.88), IGFBP2 in KK and Charoke (0.92 and 0.90, respectively), LEP1 in Charoke (0.94), LEP2 in KKC2 (0.58), LEP3 in Brakmas and KKC1 (0.70 and 0.62), LGB in KKC1 (0.82) and TG in KK (0.88). High gene flow was found between Brakmas and KKC2 (Fst=0.26), while lowest gene flow was found between KKC1 and KKC2 (Fst=0.023). Despite this, the KKC1 was found to be very similar to KKC2 (genetic distances (GD)=0.01), and Charoke was similar to Brakmas (GD=0.06). Population structure analysis of the seven breeds inferred to five clusters, with KKC1 and KKC2 being pooled together and Brangus and Cheroke, both breeds with B. taurus genes, being pooled together. The second study evaluated the Brakmas breed for birth weight (BW), 3-month weight (W3), weaning weight at 180 days of age (WW), and average daily gain from birth to 90 days of age (ADG3) and to 180 days (ADG6) using available and validated records from the year 2000 to 2009. Effect of season on all investigated traits was non-significant. The effect of sex was significant (p<0.05) for BW, W3, ADG3, ADG6, but there was no significant effect of sex on W6. Parity had a significant (p<0.01) effect only on BW. Year showed significant (p<0.01) effect on BW, W3 and ADG3. The year 2004 showed higher levels of BW and ADG in comparison of 2006 and 2007. The BW showed moderate heritability (0.30) that was higher than other traits (0.18-0.26). In conclusion result of studies confirmed the existence of polymorphism at candidate genes for traits of interest in beef cattle breeds in Malaysia. This has potential for use in the improvement of the local cattle breeds. However, the effects of these SNPs should be validated by conducting association studies. The second study showed that the Brakmas cattle has potential for improvement. With proper record keeping and utilization of estimated genetic parameters and exploitation of SNPs at candidate genes, the performance of this beef breed may be improved.